Three-Dimensional Interactive Visualization of the Thematic Network of Immersive Learning Research - Madalena Antunes de Sousa (2022)
The field of Immersive Learning Research crosses multiple scientific areas. Awareness of the interconnections of this interdisciplinary literature with standard scholarly tools is difficult. This work provides a three-dimensional interactive thematic network visualization tool for this field. It allows researchers to find which works are associated with a theme within immersive learning research, see how themes are interconnected, and do filtering by article metadata. Moreover, it enables researchers to compare theme organization by visualizing different clustering criteria. The tool was developed through application of the Design Science Research methodology, addressing theme-analysis problems found via a literature survey. A thematic node-link network was created in a previous survey research, providing themes data on Immersive Learning practices and strategies. These data were now mapped to its source articles as part of the current effort. By providing clustering, filtering, and 3D navigation features, the tool enables interactive visualization of the interconnection of the themes in the field of Immersive Learning Research, and exploration of its grounding papers. Any researcher can now filter by authors, publication outlets, institutions, and year, to analyze how themes were more or less explored/cited, and compare clustering criteria such as citation counts or total papers per theme, to acquire a clearer awareness of the field.